A Whole-genome Scan for Pulse Pressure/Stroke Volume Ratio in African Americans: The HyperGEN Study - Sherva, Richard (2007)
BACKGROUND: Arterial stiffness is reported in numerous family studies to be heritable; linkage analysis has identified genomic regions that likely harbor genes contributing to its phenotypic expression. We sought to identify loci contributing to arterial stiffness in a large group of African American hypertensive families. METHODS: We performed a genome scan on 1251 African Americans in families participating in the HyperGEN (Hypertension Genetic Epidemiology Network) study. Children of the hypertensive proband generation were also included in the analysis. Arterial stiffness was estimated as pulse pressure (PP: systolic –diastolic blood pressure) divided by echocardiographically determined stroke volume (SV). PP/SV ratio was adjusted for several non-genetic sources of variation, including demographic and lifestyle factors; the residual phenotype was analyzed using multipoint variance components linkage implemented in SOLAR 2.0.3. RESULTS: Arterial stiffness was 20% heritable in African Americans. Two regions were highly suggestive of linkage, one between markers D1S1665 and D1S1728 in the 215 cM region of chromosome 1 (LOD = 3.08), and another between D14S588 and D14S606 in the 85 cM region of chromosome 14 (LOD = 2.42). Two candidate genes (GPR-25, SMOC-1) are located in the linked regions. SMOC-1 is of physiological interest because it codes a secreted glycoprotein with five domains, each containing regions homologous to those on other proteins that mediate cell-matrix interactions. GPR-25 is homologous to receptors involved in blood pressure regulation. CONCLUSIONS: At least two chromosomal regions in humans are likely to harbor genes contributing to interindividual variation in PP/SV ratio, an index of arterial stiffness, in African Americans.